The Possibility of Interreligious Dialogue: A Philosophical Foundation - Risalatul Hukmi (Jurnal Filsafat "WISDOM", 2023)
The possibility of interreligious dialogue depends, at least, on the justification for the existence of religion itself. Thus, the constructionist theory of religion becomes a fundamental problem in constructing a framework of interreligious dialogue theory because religion is expressed as an imaginary existence, in the sense that it is only the construction of scholars and academics. If the existence of religion itself cannot be justified ontologically, it means that interreligious dialogue is impossible. Hence, to answer that problem, we inevitably have to prove ontologically the existence of religion without having to reject the constructionist theory. In this paper, I use the social ontology analysis proposed by John Searle and the historical ontology theory proposed by Ian Hacking to prove that religion as a constructed social reality exists objectively. Thus, interreligious dialogue is possible within a framework of existential hermeneutics that presupposes a process of understanding that changes continuously in accordance with historical ontology as its foundation.